Synthetic phosphopeptides: from spike-in standards to affinity tools for protein-protein interaction studies - Winter, Martin; Debus, Jürgen; Abdollahi, Amir; Schnölzer, Martina; Warnken, Uwe (Analytical biochemistry, 2019)
Synthetic isotope labeled phosphopeptides are valuable tools for the quantification and validation of phosphoproteome data. Here, we report that the same set of phosphopeptides, which are used as spike-in standards, can be successfully applied for identification of stimulus specific protein-protein interactions mediated by the respective phosphorylation sites. As a proof-of-concept, binding of two γH2AX (pS139) phosphosite specific interaction partners, MDC1 and 53BP1, was confirmed and elevated binding affinity was revealed in response to ionizing radiation. Our strategy is generally applicable and enables multiplexed validation and functional analysis of phosphorylation sites offering great potential for the follow-up of phosphoproteome studies.
Available online 28 December 2018
Gesehen am 19.09.2019